Economic Valuation of Three Coastal Tourism Objects Owned by the Local Government of Tulungagung Regency - Angga Erlando; Zaenal Fanani; Andre Pupung Darmawan; Reni Sri Hapsari; Ahmad Ibnu Riza; Annisa Nurul Hakim (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
This study aims to evaluate three beach tourism destinations managed as assets by the Tulungagung Regency Government, namely Popoh Beach, Sidem Beach, and Sine Beach, to optimize their management and revenue generation for the benefit of the community and the region. The research employs an inferential quantitative method using negative binomial regression techniques, based on primary data collected through direct visitor surveys conducted in 2023. The fundamental model is developed using the Travel cost Method (TCM) as a concept to assess demand for environmental services in the form of recreational activities. The economic valuation results show that using the TCM method, the three beaches possess moderate potential value for commercialization. However, based on the annual revenue data, the total income generated by these beaches remains below IDR 1 billion, indicating challenges in promotion/branding, management, and commercialization (sales) strategies that need to be addressed moving forward. Meanwhile, the calculation of Willingness to pay (WTP) using the Contingent Valuation Method (CVM) focuses solely on the willingness to pay for increased ticket prices. When analyzing the consumer surplus values of each beach destination, it is evident that the consumer surplus significantly exceeds the total WTP